2020
DOI: 10.1002/cpsc.120
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Protocol for 3D Retinal Organoids, Immunostaining and Signal Quantitation

Abstract: Structures resembling whole organs, called organoids, are generated using pluripotent stem cells and 3D culturing methods. This relies on the ability of cells to self-reorganize after dissociation. In combination with certain supplemented factors, differentiation can be directed toward the formation of several organ-like structures. Here, a protocol for the generation of retinal organoids containing all seven retinal cell types is described. This protocol does not depend on Matrigel, and by keeping the organoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…We noticed in the literature that a subset of factors were commonly added together to target a single pathway simultaneously, or influence multiple pathways. For example, dual SMAD inhibition by SB431542 and LDN193189 is used to regulate both the branches of the TGF-β/BMP signaling pathway, and we found that they were added exclusively together in retinal organoid protocols [107,108] (Table 1). The suppression of TGF-β and BMP signaling has also been achieved by SB431542 and dorsomorphin treatment and is used in vitro and in vivo to direct cells into the neural and retinal fates [105,268,269].…”
Section: Does the Synergistic Addition Of Multiple Factors Results In An Additive Effect Or Is It Not Necessary?mentioning
confidence: 99%
See 3 more Smart Citations
“…We noticed in the literature that a subset of factors were commonly added together to target a single pathway simultaneously, or influence multiple pathways. For example, dual SMAD inhibition by SB431542 and LDN193189 is used to regulate both the branches of the TGF-β/BMP signaling pathway, and we found that they were added exclusively together in retinal organoid protocols [107,108] (Table 1). The suppression of TGF-β and BMP signaling has also been achieved by SB431542 and dorsomorphin treatment and is used in vitro and in vivo to direct cells into the neural and retinal fates [105,268,269].…”
Section: Does the Synergistic Addition Of Multiple Factors Results In An Additive Effect Or Is It Not Necessary?mentioning
confidence: 99%
“…SB431542 is typically added to cultures within the first seven days of cultures (Table 1). It improves the development of specific retinal cell types, such as photoreceptors, both in 2D cultures and 3D retinal organoid models [107][108][109]. COCO is part of the Dan family of TGF-β antagonists [110], and is commonly used as an inhibitor of the BMP branch of the signaling pathway (Figure 3).…”
Section: Agonists and Antagonists Of The Tgfβ/bmp Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…This special collection brings together three articles on cellular differentiation and complex tissue models. Miller and colleagues report on the derivation of cardiomyocytes from pluripotent stem cells (Miller, Genehr, Telugu, Kurths, & Diecke, 2020), and Döpper and colleagues describe generation of retinal organoids that contain all seven retinal cell types (Döpper et al., 2020). Next, Applet‐Menzel and coworkers review human iPSC−derived blood‐brain barrier models as tools for preclinical drug discovery and development (Appelt‐Menzel et al., 2020).…”
Section: Introductionmentioning
confidence: 99%